Elevated monocyte HLA-DR in pediatric secondary hemophagocytic lymphohistiocytosis: a retrospective study - Raimbault, Sylvain; Monneret, Guillaume; Gossez, Morgane; Venet, Fabienne; Belot, Alexandre; Zekre, Franck; Remy, Solene; Javouhey, Etienne (Frontiers in Immunology, 2023)
Introduction Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition, and its diagnosis may be challenging. In particular, some cases show close similarities to sepsis (fever, organ failure, high ferritin), but their treatment, while urgent, differ: prompt broad-spectrum antibiotherapy for sepsis, immunosuppressive treatment in HLH. We questioned whether mHLA-DR could be a diagnostic marker for secondary HLH (sHLH). Methods We retrospectively reviewed data from patients with a sHLH diagnosis and mHLA-DR quantification. mHLA-DR data from healthy children and children with septic shock, whose HLA-DR expression is reduced, from a previously published study were also included for comparison. Results Six patients with sHLH had mHLA-DR quantification. The median level of monocyte mHLA-DR expression in sHLH patients (79,409 AB/C, IQR [75,734 - 86,453]) was significantly higher than in healthy children and those with septic shock (respectively 29,668 AB/C, IQR [24,335 - 39,199], and 7,493 AB/C, IQR [3,758 – 14,659]). Each sHLH patient had a mHLA-DR higher than our laboratory normal values. Four patients had a second mHLA-DR sampling 2 to 4 days after the initial analysis and treatment initiation with high-dose corticosteroids, for all patients mHLA-DR decreased to within or close to the normal range. One patient with systemic juvenile idiopathic arthritis had repeated mHLA-DR measurements over a 200-day period during which she underwent 4 HLH episodes. mHLA-DR increased during relapses and normalized after treatment incrementation. Conclusion In this small series, mHLA-DR was systematically elevated in sHLH patients. Elevated mHLA-DR could contribute to sHLH diagnosis and help earlier distinction with septic shock.